Outlook On Oral Health: A Questionnaire Survey Of General Population - Singh Gehlot, Mahendra; Agarwal, Amit; Sharma, Sakshi; Chaudhry, Kalpana; Sharma, Diwakar (National Journal of Community Medicine, 2021)
Introduction: Poor oral health and untreated oral conditions are not readily identifiable by general population and morbid oral status is widely accepted as a norm, creating a significant impact on quality of life. Oral diseases are a major public health concern due to their high prevalence and neglect. The outlook of people towards oral health and disease, therefore, has an important influence on dental health. Methods: A structured questionnaire was posed to general Indian population. 1008 completed responses were collected and analyzed for association amongst discreet variables using Pearson’s Chi-square test and a P-value below 0.05 was considered statistically significant. Results: The relationship between dental awareness and demographic variables like gender, socioeconomic background, and education are discussed. Awareness amongst rural and less educated populations is low. The children face dental neglect, people are unaware of the need for regular dental visits and systemic correlation of poor oral hygiene. Females are more aware of hygiene practices than male population. Conclusion: The present study found that there is an immediate need to create awareness amongst general population about the necessity to follow proper oral healthcare measures, especially amongst rural and less educated groups, parents of young children, pregnant females, and the elderly.